Iniciativas de ecodiseño en envases del sector farmacéutico para la transición hacia una economía circular (2021)
The development of the initiatives and the case studies include positive indications in terms of saving materials or raw materials, reducing the disposal of packaging waste and simplifying waste management and recycling processes with the substitution of materials. or the monomaterialization of the container. Therefore, information is presented that approximates those modifiable attributes and ecodesign options applicable to pharmaceutical grade packaging, which may represent value propositions for some divisions of the pharmaceutical industry and which respond to circular economy principles.